Evaluation of the Effectiveness of Vector Management Methods in Hospital X Batam City - Herdianti; Sari, Novela; Husein, Al Hafez (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
According to the Ministry of Health, disease vector and pest management includes all actions or activities aimed at reducing the population of disease vectors and animals as low as possible so that their presence in an area no longer poses a risk of disease transmission. The purpose of this study is to determine the Input, Process, and Output aspects of evaluating the effectiveness of vector handling methods in Hospital X in Batam City. This study used qualitative methods through in-depth interviews and observations with a total of six informants, namely the Head of Subdivision of Public Facilities, Head of Public Facilities Affairs, Health & Safety Coordinator, Human Resources, Head of Finance, 3rd agent (CV. Bumi Resik). The results of this study indicate that vector handling in Hospital X has been quite effective, lack of awareness of Human Resources of the prohibition of leaving food scraps in the work room. It is necessary to collaborate with entomologists to get advice and vector handling strategies that are more effective and specific according to the conditions of Hospital X, apply strict sanctions for those who violate the prohibition of leaving food scraps in the work room, provide informative posters in the hospital area about simple procedures that can be done to support vector handling